Fundamentals of nuclear physics - Jelley, N. A. 1946- (Cambridge University Press, 1990)
Fundamentals of Nuclear Physics is a textbook on nuclear physics aimed at undergraduates in their final year, designed to give the student a thorough understanding of the principal features of nuclei, nuclear decays and nuclear reactions. The book covers the elementary concepts of the subject necessary for introductory courses and also explores more advanced topics, suitable for graduate courses. Initially several models are described and used to explain nuclear properties with many illustrative examples. Sections follow on a-, B- and y-decay, fission, thermonuclear fusion, reactions, nuclear forces and nuclear collective motion. In each case many examples are discussed, and the student should gain a thorough grounding in knowledge of the nucleus. The presentation is quantitative and short derivations are given in full to enable the student to make predictions about nuclear phenomena. This book will be of value to all undergraduates studying nuclear physics, as well as to first-year graduates. The level of the presentation bridges the gap between introductory undergraduate and the more advanced graduate textbooks